Pandemic Covid-19, Body Immunity Response, and Herd Immunity - Rina Tri Handayani; Dewi Arradini; Aquartuti Tri Darmayanti; Aris Widiyanto; Joko Tri Atmojo (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
The World Health Organization has stated that COVID-19 is a "global pandemic". However, community attitudes and compliance in maintaining protocols during the pandemic were minimal and raised the issue of "herd immunity". What exactly is herd immunity, how exactly does the body's immune system react to COVID-19 and what is a COVID-19 pandemic? The purpose of writing articles is to provide information about the definition of a pandemic, the body's immune system in dealing with COVID-19, and herd immunity. A systematic review was carried out in May 2020 by searching databases: PubMed, google scholar, NIH, CDC, and Science Direct. Keywords: "Pandemic and COVID 19" and "COVID 19 rapid test and accuracy", "PCR accuracy" and "PCR COVID 19 vs Rapid test" and "Herd immunity". The COVID-19 pandemic occurred because there was a discovery and a new mutation of the SARS-CoV virus becoming very infectious and of high virulence. Herd Immunity cannot be said to be the relevant treatment for COVID-19. It requires a large minimum threshold of immunity to achieve Herd Immunity, and it is very unethical to allow large numbers of individuals to be infected.